Structural features of the roughness profile of hardened steel parts after finishing turning - Ovsyannikov Victor; Nekrasov Roman; Putilova Ulyana; Gubenko Arseniy (EPJ Web of Conferences)
This article presents the results of a study of the structural features of the roughness profile of surfaces that are treated with finishing turning. The processing of hardened high-quality carbon steels is considered as initial data. Standard cutting tools with mechanical plate mounting are used. The profile of the treated surface was analyzed using the theory of random processes and fractal geometry methods. As a result of the research, it was found that with a decrease in the arithmetic mean separation of the Ra profile, the proportion of the random component increases. It can be concluded that the role of vibration processes in the formation of the profile is increasing. This factor makes it possible to implement a processing management strategy with the possibility of improving the quality of the surface layer.